Pathogenicity of viral nervous necrosis virus for Guppy fish, Poecilia reticulata - Nazari, Alireza; Mohd. Daud, Hassan; Bovo, Giuseppe; Zorriehzahra, Mohammad Jalil; Tengku Ibrahim, Tengku Azmi; Arshad, Siti Suri (Iranian Fisheries Science Research Institute, 2014)
The pathogenicity of a Nervous Necrosis Virus isolate obtained from naturally infected Golden grey mullet (Liza auratus) suffering serious mortalities in Iranian coastline water of the Caspian Sea was investigated for first time. An experimental infection has been performed using three groups, two experimental groups and one control group of Guppy (Poecilia reticulata) with mean weight 0.47±0.09 g, at temperature 25°C. The infectious dosage (50 ml) with TCID50/ml=104.25 for 2 hours in group 1 and 4 hours in group 2 developed the disease with immersion method. Clear clinical signs associated with significant mortality were observed since 15 dpi. Cumulative mortalities rose to 100% at 30 dpi. While in the control group no mortality was recorded. Virus was re-isolated on SSN-1 cell line that showing typical CPE developed after inoculation with tissues filtrate from dead fish. Histopathological examination of exposed fish, showed clear vacuolization in the granular layer of the retina and cerebellum. TEM micrographs revealed intracytoplasmic vacuoles in the retina of infected Guppy. IHC revealed the presence of viral antigens in the brain and retina. These results confirmed the pathogenicity of the NNV isolate obtained from Golden grey mullet suffering high mortality with regard to suggest that the same agent isolated from golden grey mullet is very likely the cause of the mortality observed in the same species.